Blood flow changes coincide with cellular rearrangements during blood vessel pruning in zebrafish embryos. - Eva Kochhan; Anna Lenard; Elin Ellertsdottir; Lukas Herwig; Markus Affolter; Heinz-Georg Belting; Arndt F Siekmann (PLoS ONE)
After the initial formation of a highly branched vascular plexus, blood vessel pruning generates a hierarchically structured network with improved flow characteristics. We report here on the cellular events that occur during the pruning of a defined blood vessel in the eye of developing zebrafish embryos. Time-lapse imaging reveals that the connection of a new blood vessel sprout with a previously perfused multicellular endothelial tube leads to the formation of a branched, Y-shaped structure. Subsequently, endothelial cells in parts of the previously perfused branch rearrange from a multicellular into a unicellular tube, followed by blood vessel detachment. This process is accompanied by endothelial cell death. Finally, we show that differences in blood flow between neighboring vessels are important for the completion of the pruning process. Our data suggest that flow induced changes in tubular architecture ensure proper blood vessel pruning.